2004
DOI: 10.21236/ada427989
|View full text |Cite
|
Sign up to set email alerts
|

Inspections of Previously Monitored Rubble-Mound Coastal Structures

Abstract: ABSTRACT:This report presents results of inspections of rubble-mound coastal structures monitored previously under the Monitoring Completed Navigation Projects (MCNP) Program. Expedient, low-cost walking inspections were performed at 11 sites. Positions of breakwater and jetty armor units were compared with their positions in previous aerial photography and photogrammetric surveys. Settlement of portions of the structures as well as voids in their armor cover also was noted, and photographs of the structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They also found 33 broken dolosse cast in 1974. Bottin and Tolliver (1999) and Bottin et al (2004) found no additional breakage over the 1993 survey. However, their surveys were limited to casual observations from on-site and careful comparison with aerial photographs.…”
Section: Broken Armor Unit Surveymentioning
confidence: 91%
“…They also found 33 broken dolosse cast in 1974. Bottin and Tolliver (1999) and Bottin et al (2004) found no additional breakage over the 1993 survey. However, their surveys were limited to casual observations from on-site and careful comparison with aerial photographs.…”
Section: Broken Armor Unit Surveymentioning
confidence: 91%
“…In June 2004, a walking inspection of the Cleveland Harbor East Breakwater was conducted. Results and recommendations are summarized by Bottin et al (2004) as follows:…”
Section: Cleveland Harbor East Breakwater 2004 Periodic Inspections Wmentioning
confidence: 99%
“…Comparison views of the breakwater are shown in Figures 24 and 25. Results and suggestions are summarized by Bottin et al (2004) as follows:…”
Section: Burns Harbor North Breakwater 2004 Periodic Inspections Walkmentioning
confidence: 99%